Sovereignty, power, and authority: understanding the conversion of Hagia Sophia from a performative perspective - Oztig, Lacin Idil; Adisonmez, Umut Can (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Throughout its history, Hagia Sophia has been used as an Orthodox church, a Roman Catholic church, a mosque, and a museum. After a controversial decision in 2020, Hagia Sophia was converted back into a mosque. This article shows that Hagia Sophia's conversion into a mosque is more than a juridical action. By adopting a performative approach, it is argued that, through the conversion, the ruling Justice and Development Party seeks to achieve its two-fold agenda. Firstly, while reflecting the party's Islamic political vision that situates religion as an integral part of everyday life, this move reaffirms the JDP's position as the ultimate political authority that shapes Turkey's sovereign space. Secondly, the conversion fits into and perpetuates the JDP's instrumentalization of religion as a political tool to increase its power in the Middle East and North Africa (MENA) region in line with its neo-Ottomanist agenda.
Keywords: Hagia Sophia; performative approach; sovereignty; religion; soft power; STATE; Area Studies